The impact of Consumer Awareness on buying behavior of green products (International Journal of Scientific Research and Management (IJSRM), 2018)
Consumer awareness towards the organic, eco-friendly or green products is important in guiding them towards the purchase intention and further favors the buying behavior. This study aims to identify the influence of consumer’s environmental concerns, awareness of green product, and brand image on their buying decision of eco-friendly products. Companies try to produce natural products to meet the need and satisfaction of the people. Major determinants that impacts consumer awareness and further leads them to buy green products are safety, income, ecological concern, knowledge, age , gender, attitude, values, brand labelling, packaging etc. this study provides valuable insights into the consumer buying behavior by studying the consumer awareness. Compared to consumer awareness in developed countries Indian consumers are still less aware of the environmental issues. This paper reviews the work of researches and aims to define the impact consumer awareness have on the purchasing behavior of the organic or green products.